PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI DENGAN MODEL THINK TALK WRITE (TTW) DI KELAS IV SD NEGERI 29 DADOK TUNGGUL HITAM KOTA PADANG - Apriani Maulana, Puji; Adrias; kharisma, inggria; Habibi, M (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low narrative writing skills of fourth-grade students at SD Negeri 29 Dadok Tunggul Hitam, Padang. The students experienced difficulties in generating story ideas, organizing narrative structures coherently, selecting appropriate vocabulary, and applying correct spelling and punctuation according to Indonesian language conventions. This study aimed to describe the improvement of students' narrative writing skills through the implementation of the Think Talk Write (TTW) learning model, covering the aspects of lesson planning, learning implementation, and learning outcomes. This study employed Classroom Action Research (CAR) using qualitative and quantitative approaches. The research was conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The participants were one classroom teacher and 28 fourth-grade students of SD Negeri 29 Dadok Tunggul Hitam, Padang, during the second semester of the 2025/2026 academic year. Data were collected through classroom observations, performance assessments, documentation, and field notes, and were analyzed using qualitative and quantitative techniques. The findings revealed that the implementation of the Think Talk Write (TTW) model improved the quality of lesson planning, classroom implementation, and students' narrative writing skills. The average writing score increased from 70.11 in Cycle I Meeting 1 to 75.38 in Cycle I Meeting 2 and further improved to 88.83 in Cycle II. Improvements were also observed in all assessment aspects, including idea generation, outline development, narrative organization, story sequencing, appropriate word and sentence usage, and the application of spelling and punctuation. Therefore, the Think Talk Write (TTW) model was effective in improving the narrative writing skills of fourth-grade students at SD Negeri 29 Dadok Tunggul Hitam, Padang.